A study on Pasteurellosis in a commercial rabbit unit - SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ), K.; ILIADIS (Ν. ΗΛΙΑΔΗΣ), N.; VLEMAS (Ι. ΒΛΕΜΜΑΣ), I.; SIDIROPOULOU (Α. ΣΙΔΗΡΟΠΟΥΛΟΥ), A.; KYRIAKIS (Σ.K. ΚΥΡΙΑΚΗΣ), S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
This paper studies Pasteurellosis in a commercial rabbit unit, one of the most important and common diseases of rabbits. The morbidity within the 2216 animals of the unit was 8,1%, while the mortality was 58,8%. The percentage of the morbidity tended to increase along with the age of the animals, but this was not statistically significant. It was 11,6% at the age of weaning and 15,48% at the age of fattening. The morbidity of the breeding animals was 10,5%. The clinical findings of the infected rabbits included rhinitis, keratoconjunctivitis, otitis media, pneumonia, enteritis, metritis and subcutaneous abscesses. Thirty seven rabbits were subjected to postmortem examination and the characteristic lesions of Pasteurellosis were observed. Samples of the organs of infected rabbits were used for microbiological examinations by which Pasteurella multocida was isolated.